Penerapan Teknologi Single Sign On (SSO)dengan Metode JSON Web Token untuk Meningkatkan Kemudahan Akses Pengguna - Vidya Meidita; Samsul Arifin; Dian Wahyuningsih; Dinny Wahyu Widarti (Teknologi Informasi : Teori, Konsep, dan Implementasi : Jurnal Ilmiah, 2026)
This study implements Single Sign-On (SSO) technology using the JSON Web Token (JWT) method at VINSCODE, a software house, to address user difficulties in managing multiple accounts and passwords. The research aims to improve access efficiency and reduce account security risks by integrating JWT into the SSO system. Functional testing, usability testing, and user questionnaires were conducted to measure the system's performance across three indicators: ease of access, logging and tracking, and data security. The results show that users can log in once and move between integrated  websites  without  re-authentication,  with  all  activities  accurately  logged.  Security  is enhanced through a verification code sent to users during the first login from a new device. Questionnaire results indicate a high user satisfaction rate, with an average score of 85%, showing improvements   in   login   convenience,   account   management,   and   system   monitoring.   The implementation has proven effective in increasing access efficiency and ensuring secure user authentication across applications.